Pelatihan Penerapan Teknologi Augmented Reality dalam Pendidikan Bahasa Indonesia di Wilayah Kecamatan Batang-Batang Kabupaten Sumenep - Wardi, Moh.; Sumitro, Eko Adi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STAI Al Fithrah Surabaya, 2025)
This community service project aims to enhance the competence of Indonesian language teachers in integrating Augmented Reality (AR) technology into the learning process. The methods employed include participatory training, hands-on media development using Assemblr Edu, and continuous mentoring through both face-to-face and online sessions. These three methods are systematically integrated: the training provides theoretical and technical foundations, the hands-on sessions build practical skills in AR media development, and the mentoring ensures sustainable implementation and adaptation to classroom challenges. The results demonstrate a significant improvement in teachers’ understanding and skills in applying AR, as reflected in pre- and post-test score gains and the production of concrete learning modules. The application of these AR-based media in classrooms has created a more interactive and contextual learning environment, increasing students’ engagement and comprehension of Indonesian language content. In the long term, this initiative has the potential to foster a culture of innovation within partner schools, enhance teachers’ digital literacy, and expand the adoption of educational technology. The availability of AR modules, documentation of best practices, and sustained mentoring are key factors in ensuring the long-term benefits of this program.